Pengaruh Pemberian Asupan Medium Chain Fatty Acids (Mcfa) Terhadap Tekanan Darah Penderita Hipertensi - Rusnelly, Rusnelly,; Rohanta Siregar; Mardiana Mardiana (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2014)
This study aimed to determine the effect of the intake of Medium Chain Fatty Acids (MCFA) on blood pressure. This research was designed in quasiexperimental with two groups. They were 30 people as treatment group and a comparison group of 30 people.Treatment group have to drunk of coconut oil 50 ml a day for 3 days and nutritional counseling, and the ather group was only given nutritional counseling. This research has been done on Ocktober 2013 until December 2013 at Puskesmas Sosial in Palembang South Sumatera Province. Data were analyzed by T test Paired to knew a diferent blood pressure after consumed Medium Chain Fatty Acids (MCFA) in three days and T test independent to knew different blood pressure betwen treatment group and comparison group. The results of this study found that was a significant effectof MCFA feeding on blood pressure in the treatment group (P<0.05) and significant differences (P <0.05) blood pressure after treatment between the treatment group and the comparison group were found.